Choosing wisely: The Canadian Thoracic Society's list of six things that physicians and patients should question. Issue 2 (3rd April 2017) - Gupta, Samir; Goodridge, Donna; Pakhalé, Smita; McIntyre, Kieran; Pendharkar, Sachin R.
ABSTRACT: Choosing Wisely is a campaign that aims to help clinicians and patients engage in conversations regarding unnecessary tests and treatments, in order to improve quality of care and reduce waste in healthcare. Specialty societies are asked to develop lists of commonly used tests and treatments that are not supported by evidence and/or could expose patients to unnecessary harm. The Canadian Thoracic Society appointed a 5-member Choosing Wisely Task Force to develop this list. After establishing evidence-based criteria for recommendation selection and prioritization, they generated an initial list of candidate recommendations from: 1) existing respiratory-related US and Canadian Choosing Wisely recommendations; 2) Canadian Medical Association (CMA) Patient-Oriented Evidence that Matters (POEMs™) rated by ≥ 10% of CMA respondents to: "… help to avoid unnecessary or inappropriate treatment, diagnostic procedures, preventative interventions or a referral…"; and 3) additional suggestions by CTS content experts. The list was serially reduced through voting by members of the Canadian Respiratory Guidelines Committee and the Task Force in three electronic Delphi processes and by members of the CTS in an online poll (members were also asked to suggest additional recommendations). Evidence reviews were performed for the top 10 recommendations. This resulted in the following CTS Choosing Wisely Top 6 List: 1) Don't initiate long-term maintenance inhalers in stable patients with suspected COPD if they have not had confirmation of post-bronchodilator airflow obstruction with spirometry; 2) Don't perform CT screening for lung cancer among patients at low risk for lung cancer; 3) Don't perform chest computed tomography (CT angiography) or ventilation-perfusion scanning to evaluate for possible pulmonary embolism in patients with a low clinical probability and negative results of a highly sensitive D-dimer assay; 4) Don't treat adult cough with antibiotics even if it lasts more than 1 week, unless bacterial pneumonia is suspected (mean viral cough duration is 18 days); 5) Don't initiate medications for asthma (e.g., inhalers, leukotriene receptor antagonists, or other) in patients ≥ 6 years old who have not had confirmation of reversible airflow limitation with spirometry, and in its absence, a positive methacholine or exercise challenge test, or sufficient peak expiratory flow variability; and 6) Don't use antibiotics for acute asthma exacerbations without clear signs of bacterial infection. This list was developed through a rigorous and novel process and addresses overuse in different areas of respiratory medicine in Canada. It can provide a starting point for a systematic implementation process targeting clinicians and patients, to the benefit of patients and the healthcare system in general.